2023
DOI: 10.3390/ijms242015493
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Antibiotic and Non-Antibiotic Compounds Improves Antibiotic Efficacy against Multidrug-Resistant Bacteria

Gang Xiao,
Jiyun Li,
Zhiliang Sun

Abstract: Bacterial antibiotic resistance, especially the emergence of multidrug-resistant (MDR) strains, urgently requires the development of effective treatment strategies. It is always of interest to delve into the mechanisms of resistance to current antibiotics and target them to promote the efficacy of existing antibiotics. In recent years, non-antibiotic compounds have played an important auxiliary role in improving the efficacy of antibiotics and promoting the treatment of drug-resistant bacteria. The combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 275 publications
0
5
0
Order By: Relevance
“…The synergy between antibiotics and AMPs could be due to the increase permeability of the antibiotic by the AMP due to a pore formation or cell wall degradation (e.g., in the case of antimicrobials that acts on the transcription and replication). In addition, some antibiotics, such as gentamicin, produce a lipid aggregation that increases the permeabilizing capabilities of the AMP due to a major integration on the lipid bilayer, and by disturbing bacterial metabolism, which leads to a poor efficient production of enzymes synthesis and produces a synergistic activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The synergy between antibiotics and AMPs could be due to the increase permeability of the antibiotic by the AMP due to a pore formation or cell wall degradation (e.g., in the case of antimicrobials that acts on the transcription and replication). In addition, some antibiotics, such as gentamicin, produce a lipid aggregation that increases the permeabilizing capabilities of the AMP due to a major integration on the lipid bilayer, and by disturbing bacterial metabolism, which leads to a poor efficient production of enzymes synthesis and produces a synergistic activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…An essential oil's ability to combat germs is directly related to its chemical makeup, the main compounds' functional groups, and the way these components work together. This synergy can arise from several processes, including the inhibition of metabolic pathways or the agents involved, as well as the disruption of the bacterial cell membrane, which makes it easier for additional antibacterial agents to work against the bacterium [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of action of phenolic compounds contained in plant extracts on the bacterial cell have been attributed in part to damage to the bacterial membrane, inhibition of virulence factors (such as enzymes and toxins), and inhibition of bacterial biofilm formation [43,44]. Numerous reports in the literature have shown that polyphenolic compounds isolated from plants, in combination with commonly used antibiotics, may represent a new strategy against infections caused by multidrug-resistant bacteria (Staphylococcus aureus, Escherichia coli, or Pseudomonas aeruginosa) [44][45][46].…”
Section: Discussionmentioning
confidence: 99%